The Impact of Sharia Working Capital Financing and SME Investments on Economic Growth in South Sulawesi - Suharli; Rini Idayanti; Irma, Irma; Nur Wahyu (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to: (1) examine the effect of Islamic working capital financing on economic growth in South Sulawesi; (2) explain the effect of Micro, Small, and Medium Enterprises (MSMEs) investment on economic growth in the region; and (3) describe how the combination of Islamic working capital financing and MSME investment from Islamic Commercial Banks (BUS) and Islamic Business Units (UUS) affects economic growth in South Sulawesi. This research was conducted from August to September 2023 using quantitative descriptive methodology. Data on the level of economic growth was obtained from the South Sulawesi Central Statistics Agency (BPS). A non-probability sample of 32 was taken using saturated sampling technique from quarterly financial reports. The data collection methods used were documentation and observation. Data analysis was performed using multiple linear regression analysis on SPSS 20 by IBM. The research findings show that: (1) partially, Islamic working capital financing has a negative and significant impact on economic growth in South Sulawesi; (2) partially, MSME investment has a positive but insignificant impact on economic growth in South Sulawesi; and (3) simultaneously, Islamic working capital financing and MSME investment have a positive and significant impact on economic growth in South Sulawesi.